Association between thyroid dysfunction and prognosis in patients with liver failure: a systematic review and meta-analysis - Bao, Shaoyin; Pan, Yin; Ruan, Yanyun; Hassan, Hozeifa Mohamed; Lu, Hongsheng; Chen, Qi (Frontiers in Endocrinology, 2026)
ObjectiveTo systematically evaluate the association between thyroid dysfunction and prognosis in patients with liver failure.MethodsWe systematically searched PubMed, Embase, Web of Science (WOS), and China National Knowledge Infrastructure (CNKI) till August 2025 to identify prospective or retrospective studies assessing the relationship between thyroid function—specifically, thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4)—and outcomes in adult patients with liver failure, including mortality, intensive care unit (ICU) admission, and organ failure. Study quality was evaluated using the Newcastle–Ottawa Scale (NOS). Pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated, and heterogeneity, subgroup, and sensitivity analyses were conducted.ResultsEleven studies, including 3,595 patients from four countries, were included. Thyroid dysfunction was significantly associated with increased mortality in patients with liver failure (RR = 3.56, 95% CI: 2.77–4.57; I² = 36%). Subgroup analyses by sex, FT3 cut-off, and etiology (hepatitis B virus [HBV] vs. non-hepatitis B virus acute-on-chronic liver failure [non-HBV ACLF]) showed consistent associations. Additionally, a subgroup analysis comparing FT3 concentrations between survival and death groups in liver failure patients revealed a significant difference in FT3 levels between the two groups (mean difference [MD] = 0.89 [0.41, 1.37] for short-term mortality and MD = 0.42 [0.23, 0.61] for long-term mortality). Sensitivity analyses confirmed the robustness of the results. No substantial publication bias was observed.ConclusionsThyroid dysfunction, particularly low FT3 levels, is associated with higher mortality rates in patients with liver failure. These findings suggest that routine thyroid function assessment may help identify high-risk patients. Further well-designed prospective studies are needed to clarify the underlying mechanisms and evaluate the potential therapeutic implications.